Determination of Water-Soluble Vitamins B1, B2, B3, B6, B9, B12 and C on ODS Column 5 μm by High Performance Liquid Chromatography with UV-DAD Detection - Antakli1, Saad; Sarkees2, Nazeera; Sarraf1, Tereza (Asian Journal of Chemistry, 2014)
HPLC method was developed and applied to the determination of some water-soluble vitamins (B1, B2, B3, B6, B9, B12 and C) in Syrian pharmaceutical preparations. Reserved phase, ion-pair high performance liquid chromatography with UV-DAD detection was employed. The developed chromatographic method employed an ODS column with dimension (150 × 4.6 mm; 5 μm). The mobile phase was 5.3 mM of hexane-1-sulfonic acid sodium with 0.1 % triethylamine as solvent (A) at pH 3.3 and 5.3 mM of hexane-1-sulfonic acid sodium:acetonitrile (50:50) with 0.1 % triethylamine as solvent (B) at pH 3.5 and paracetamol as internal standard. The method showed acceptable values for precision, recovery and sensitivity.